CD36 may determine our desire for dietary fats - Abumrad, Nada A. (The Journal of Clinical Investigation, 2005)
There is a strong link between high fat intake and obesity. In addition to its high caloric density, dietary fat has a hyperphagic effect, in part as a result of its high palatability. The recent identification by Laugerette et al. of CD36 as a taste receptor for fatty acids provides insight into the molecular basis of our preference for fat. As we gain more information regarding the function of this receptor, we may be able to devise better strategies to address the addictive potential of dietary fat.